Anthracite-based hard carbon sodium battery negative electrode material and preparation method thereof, sodium ion battery negative electrode and sodium ion battery

Through activation treatment and chemical activation treatment, the microstructure of anthracite is regulated, combined with high-temperature carbonization treatment, the problem of insufficient sodium storage capacity of sodium-electrode materials prepared by anthracite is solved, and excellent electrochemical performance is achieved.

CN119551675APending Publication Date: 2025-03-04GUANGDONG YINA NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411401259.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing sodium-electrode materials prepared by anthracite are insufficient in their sodium storage capacity, and it is difficult to have excellent reversible specific capacity, first charge and discharge efficiency and rate performance.

Method used

The microstructure of anthracite is regulated through activation treatment and chemical activation treatment, disordered micrographite domains and closed pore structures with expanded layer spacing are formed, and the ratio of closed voids and open pores is regulated through high-temperature carbonization treatment.

Benefits of technology

It significantly improves the sodium storage capacity of anthracite-based hard carbon sodium electro-negative electrode material, and achieves excellent reversible specific capacity, first charge and discharge efficiency and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075335020000111
    Figure BDA0005075335020000111
  • Figure HDA0005075335060000011
    Figure HDA0005075335060000011
  • Figure HDA0005075335060000012
    Figure HDA0005075335060000012
Patent Text Reader

Abstract

The invention provides an anthracite-based hard carbon sodium battery negative electrode material and a preparation method thereof, a sodium ion battery negative electrode and a sodium ion battery. The preparation method comprises the following steps: S1, activation treatment: activating anthracite powder; s2, chemical activation treatment: uniformly mixing the activated anthracite powder with an alkali solution to obtain a mixture; s3, pre-carbonization treatment: putting the mixture obtained in the step S2 in inert gas for pre-carbonization treatment; s4, sequentially carrying out acid pickling treatment on the mixture subjected to pre-carbonization treatment, then washing with water until the mixture is neutral, and drying; and S5, performing high-temperature carbonization treatment: performing high-temperature carbonization treatment on the material dried in the step S4 under inert gas to obtain the anthracite-based hard carbon sodium battery negative electrode material. The anthracite-based hard carbon sodium battery negative electrode material prepared by the invention has excellent reversible specific capacity, initial charge-discharge efficiency and rate capability when being applied to a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to an anthracite-based hard carbon sodium negative electrode material and a preparation method thereof, a sodium ion battery negative electrode and a sodium ion battery. Background Art

[0002] Lithium-ion batteries have remarkable electrochemical properties such as high operating voltage, long cycle life and high energy density, but their high price, limited reserves and uneven distribution pose great challenges to their further development to meet the growing demand. Sodium-ion batteries are expected to become the next generation of electrochemical energy storage technology due to their abundant sodium reserves and compatibility with mature lithium-ion battery technology. However, the development of sodium-ion batteries is limited by their negative electrode materials.

[0003] Among many negative electrode materials, carbon materials are considered to be the most promising candidates for sodium ion storage due to their chemical stability, relative abundance and high sodium storage capacity. Hard carbon, in particular, has attracted extensive attention due to its large interlayer space and abundant lattice defects, which allow more sodium ions to be inserted into the carbon lattice. Anthracite is abundant in resources, low in impurities and is a native graphite crystal. It is currently the most cost-effective ideal precursor for preparing hard carbon. However, the carbon materials made from anthracite have a high degree of graphitization, which limits its sodium storage capacity as a negative electrode for sodium batteries.

[0004] Therefore, how to improve the sodium storage capacity of negative electrode materials prepared from anthracite and obtain a negative electrode material with excellent reversible specific capacity, initial charge and discharge efficiency and rate performance is a problem that needs to be solved urgently. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an anthracite-based hard carbon sodium negative electrode material and a preparation method thereof. The preparation method can improve the sodium storage capacity of the negative electrode material prepared from anthracite. The negative electrode material obtained by the preparation method is applied to sodium batteries and has excellent reversible specific capacity, initial charge and discharge efficiency and rate performance.

[0006] The technical solution adopted by the present invention to solve the above problems is as follows:

[0007] A method for preparing anthracite-based hard sodium carbon negative electrode material comprises the following steps:

[0008] S1. Activation treatment: Activate the anthracite powder;

[0009] S2. Chemical activation treatment: mixing the activated anthracite powder with an alkali solution to obtain a mixture;

[0010] S3 pre-carbonization treatment: the mixture obtained in step S2 is placed under an inert gas for pre-carbonization treatment;

[0011] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral and dried;

[0012] S5. High-temperature carbonization treatment: The material dried in step S4 is placed under an inert gas for high-temperature carbonization treatment to obtain an anthracite-based hard sodium carbon negative electrode material.

[0013] Furthermore, the particle size D of the anthracite powder is 50 The present invention selects the particle size D 50 The anthracite powder is 6 to 10 μm, which prevents the quality change of active substances caused by uneven particles and ensures the accuracy of test results and the stable release of material properties.

[0014] Specifically, the anthracite powder can be obtained by ball milling or air flow pulverizing of lump anthracite, which is not limited in the present invention.

[0015] Furthermore, the activation process is a gas activation process or a chemical solution activation process.

[0016] Furthermore, the gas activation treatment includes: placing the anthracite powder under activation gas, heating it to 200-400° C. at a heating rate of 1-5° C. / min, and keeping it warm for 1-10 hours.

[0017] Furthermore, the activation gas is one of air and ammonia.

[0018] Furthermore, the chemical solution activation treatment includes: mixing anthracite powder with an acid solution at a temperature of 60 to 80° C. for 6 to 12 hours, and then washing with water until neutral and drying.

[0019] In the above technical solution, the present invention provides active sites for subsequent chemical activation treatment through activation treatment, and adopts a longer constant temperature time to ensure the uniformity of the reaction.

[0020] Furthermore, the acid solution is at least one of a nitric acid solution and a phosphoric acid solution.

[0021] Preferably, the concentration of the acid solution is 4-8 mol / L.

[0022] Preferably, the drying temperature is 80° C. and the drying time is 12 hours.

[0023] Furthermore, the alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution.

[0024] Preferably, the concentration of the alkaline solution is 4-8 mol / L.

[0025] Furthermore, the chemical activation treatment in step S2 further includes subjecting the mixture to freeze drying or water bath evaporation, wherein the freeze drying or water bath evaporation is performed to remove water from the mixture.

[0026] Furthermore, the inert gas is nitrogen or argon.

[0027] Furthermore, the pre-carbonization treatment includes: heating to 500-900° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 1-10 hours.

[0028] Furthermore, the high temperature carbonization treatment includes: heating to 900-1500° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 1-4 hours.

[0029] An anthracite-based hard sodium carbon negative electrode material prepared by any one of the above-mentioned preparation methods.

[0030] A sodium ion battery negative electrode comprises the anthracite-based hard carbon sodium negative electrode material.

[0031] A sodium ion battery comprises the above-mentioned sodium ion battery negative electrode.

[0032] The present invention has the following beneficial effects:

[0033] The present invention introduces heteroatoms and rich functional groups by subjecting anthracite powder to low-temperature activation treatment, inhibits the orderly growth of subsequent carbonized microcrystals and expands the interlayer spacing, and provides more active sites for the next step of chemical activation treatment; the present invention realizes the regulation of the microstructure of anthracite by combining activation treatment with chemical activation treatment, forming disordered micrographite domains with enlarged interlayer spacing and structural characteristics of closed pores surrounded by short-range structures, thereby improving the overall electrochemical performance. The present invention forms different rich pore structures by controlling different low-temperature activation treatments, and then regulates the ratio of closed voids and open pores by combining high-temperature carbonization treatment, wherein a part of the open nanopores and ordered carbon crystals are converted into closed pores surrounded by short-range carbon structures, and another part of the open pore structure provides a fast reaction channel for sodium ion transmission, which helps to improve and optimize the electrochemical performance. The anthracite-based hard carbon sodium negative electrode material prepared by the present invention has excellent reversible specific capacity, first charge and discharge efficiency and rate performance when applied to sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The first charge and discharge curve diagram of Examples 1 to 4 of the present invention;

[0035] Figure 2 The first charge and discharge curves of comparative examples 1 to 10 of the present invention are shown;

[0036] Figure 3 This is a rate performance data diagram of Example 1 of the present invention;

[0037] Figure 4 This is a long cycle test curve diagram of Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The following will clearly and completely describe the concept of the present invention and the technical effects produced in combination with the embodiments and drawings, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0039] Unless otherwise specified, the test materials, reagents, methods and equipment used in the following examples are conventional test materials, reagents, methods and equipment in the technical field; unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial channels.

[0040] Example 1

[0041] S1. Activation process: Change the particle size D 50 Anthracite powder with a size of 6 μm was placed in an alumina sagger and heated to 350°C at a heating rate of 5°C / min in an air atmosphere for 10 h.

[0042] S2. Chemical activation treatment: The activated anthracite powder was mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0043] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0044] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0045] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0046] Example 2

[0047] S1. Activation process: Change the particle size D 50Anthracite powder with a size of 6 μm was placed in an alumina sagger, and heated to 350 °C at a rate of 5 °C / min in an atmosphere with a gas flow rate of 40 SCCM and an NH3 / Ar ratio of 1:9, and kept warm for 2 h.

[0048] S2. Chemical activation treatment: The activated anthracite powder was mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0049] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0050] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0051] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0052] Example 3

[0053] S1. Activation treatment: At a temperature of 80°C, 50 6μm anthracite powder was mixed with 6mol / L nitric acid solution and stirred for 12h, then washed and filtered to neutrality, and dried at 80℃ for 12h;

[0054] S2. Chemical activation treatment: The activated anthracite powder was mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0055] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0056] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0057] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0058] Example 4

[0059] S1. Activation treatment: At a temperature of 80°C, 506μm anthracite powder was mixed with 6mol / L phosphoric acid solution and stirred for 12h, then washed and filtered to neutrality, and dried at 80℃ for 12h;

[0060] S2. Chemical activation treatment: The activated anthracite powder was mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0061] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0062] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0063] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0064] Comparative Example 1

[0065] S1. Activation process: Change the granularity D 50 Anthracite powder with a size of 6 μm was placed in an alumina sagger and heated to 150°C at a heating rate of 5°C / min in an air atmosphere for 10 h.

[0066] S2. Chemical activation treatment: The activated anthracite powder was mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0067] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0068] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0069] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0070] Among them, the difference between Comparative Example 1 and Example 1 is that: in the process of preparing anthracite-based hard carbon sodium negative electrode material, the heating temperature in the activation treatment of step S1 is different, which is 350°C in Example 1 and 150°C in Comparative Example 1.

[0071] Comparative Example 2

[0072] S1. Activation treatment: At a temperature of 80°C, 50 6μm anthracite powder was mixed with 3mol / L nitric acid solution and stirred for 12h, then washed and filtered to neutrality, and dried at 80℃ for 12h;

[0073] S2. Chemical activation treatment: The activated anthracite powder was mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0074] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0075] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0076] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0077] Among them, the difference between Comparative Example 2 and Example 3 is that: in the process of preparing anthracite-based hard carbon sodium negative electrode material, the concentration of nitric acid solution used in the activation treatment of step S1 is different, which is 6 mol / L in Example 3 and 3 mol / L in Comparative Example 2.

[0078] Comparative Example 3

[0079] S1. Activation process: Change the granularity D 50 Anthracite powder with a size of 6 μm was placed in an alumina sagger and heated to 350°C at a heating rate of 5°C / min in an air atmosphere for 10 h.

[0080] S2. Chemical activation treatment: The activated anthracite powder was mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0081] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0082] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0083] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 6 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0084] Among them, the difference between Comparative Example 3 and Example 1 is that: in the process of preparing anthracite-based hard carbon sodium negative electrode material, the insulation time in the high-temperature carbonization treatment in step S5 is different, which is 2 hours in Example 1 and 6 hours in Comparative Example 3.

[0085] Comparative Example 4

[0086] S1. Chemical activation treatment: the particle size D 50 Anthracite powder with a size of 6 μm is uniformly mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0087] S2. Pre-carbonization treatment: The mixture obtained in step S1 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0088] S3. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0089] S4. Activation treatment: The dried material in step S3 is placed in an alumina sagger, and heated to 350°C at a heating rate of 5°C / min in an air atmosphere, and kept warm for 10h;

[0090] S5. High temperature carbonization treatment: The material obtained in step S4 is placed in a nitrogen atmosphere for high temperature carbonization treatment, the temperature is increased to 1200°C at a heating rate of 1°C / min, and the temperature is kept for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0091] Among them, the difference between Comparative Example 4 and Example 1 is that the preparation steps are different; in the process of preparing anthracite-based hard carbon sodium negative electrode material, Comparative Example 4 places the activation treatment of step S1 in the original preparation method between the pre-carbonization treatment and the high-temperature carbonization treatment.

[0092] Comparative Example 5

[0093] S1. Chemical activation treatment: the particle size D 50 Anthracite powder with a size of 6 μm is uniformly mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0094] S2. Pre-carbonization treatment: The mixture obtained in step S1 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0095] S3. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0096] S4. Activation treatment: The dried material in step S3 was mixed with 6 mol / L nitric acid solution and stirred for 12 h, then washed with water and filtered to neutrality, and dried at 80 ° C for 12 h;

[0097] S5. High-temperature carbonization treatment: The material obtained in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, the temperature is increased to 1200°C at a heating rate of 1°C / min, and the temperature is kept for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0098] Among them, the difference between Comparative Example 5 and Example 3 is that the preparation steps are different; in the process of preparing anthracite-based hard carbon sodium negative electrode material, Comparative Example 5 places the activation treatment of step S1 in the original preparation method between the pre-carbonization treatment and the high-temperature carbonization treatment.

[0099] Comparative Example 6

[0100] S1. Chemical activation treatment: the particle size D 50 Anthracite powder with a size of 6 μm is uniformly mixed with 8 mol / L sodium hydroxide solution, and then freeze-dried to obtain a mixture;

[0101] S2. Pre-carbonization treatment: The mixture obtained in step S1 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0102] S3. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0103] S4. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min and kept warm for 2h; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0104] Among them, the difference between Comparative Example 6 and Example 1 is that: the preparation method is different; in the process of preparing anthracite-based hard carbon sodium negative electrode material, the anthracite powder in Comparative Example 6 is not activated.

[0105] Comparative Example 7

[0106] S1. Activation process: Change the particle size D 50 Anthracite powder with a size of 6 μm was placed in an alumina sagger and heated to 350°C at a heating rate of 5°C / min in an air atmosphere for 10 h.

[0107] S2. High-temperature carbonization treatment: The material obtained in step S1 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, the temperature is increased to 1200°C at a heating rate of 1°C / min, and the temperature is kept for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0108] Among them, the difference between Comparative Example 7 and Example 1 is that: the preparation method is different; in the process of preparing the anthracite-based hard carbon sodium negative electrode material, Comparative Example 7 does not perform chemical activation treatment and pre-carbonization treatment.

[0109] Comparative Example 8

[0110] S1. Activation treatment: At a temperature of 80°C, 50 6μm anthracite powder was mixed with 6mol / L nitric acid solution and stirred for 12h, then washed and filtered to neutrality, and dried at 80℃ for 12h;

[0111] S2. High-temperature carbonization treatment: The material obtained in step S1 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, the temperature is increased to 1200°C at a heating rate of 1°C / min, and the temperature is kept for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0112] Among them, the difference between Comparative Example 8 and Example 3 is that: the preparation method is different; in the process of preparing the anthracite-based hard carbon sodium negative electrode material, Comparative Example 8 does not perform chemical activation treatment and pre-carbonization treatment.

[0113] Comparative Example 9

[0114] S1. Activation process: Change the granularity D 50 Anthracite powder with a size of 6 μm was placed in an alumina sagger and heated to 350°C at a heating rate of 5°C / min in an air atmosphere for 10 h.

[0115] S2. Chemical activation treatment: The activated anthracite powder is mixed with solid sodium hydroxide to obtain a mixture;

[0116] S3 pre-carbonization treatment: The mixture obtained in step S2 was placed in a nitrogen atmosphere for pre-carbonization treatment, and the temperature was raised to 600°C at a heating rate of 5°C / min and kept for 3h;

[0117] S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral, and dried at 80°C for 12h;

[0118] S5. High-temperature carbonization treatment: The material dried in step S4 is placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature is increased to 1200°C at a heating rate of 1°C / min, and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material is obtained.

[0119] Among them, the difference between Comparative Example 9 and Example 1 is that the specific method of chemical activation treatment in the preparation process is different; Comparative Example 9 chooses to mix the activated anthracite powder with solid sodium hydroxide evenly, while Example 1 mixes the activated anthracite powder with 8 mol / L sodium hydroxide solution evenly; compared with the treatment method of Comparative Example 9, the treatment method of Example 1 can mix the activated anthracite powder with sodium hydroxide more fully and evenly, which is helpful to regulate the microstructure of anthracite.

[0120] Comparative Example 10

[0121] S1. High temperature carbonization treatment: the particle size D 50 Anthracite powder with a size of 6 μm was placed in a nitrogen atmosphere for high-temperature carbonization treatment, and the temperature was increased to 1200°C at a heating rate of 1°C / min and kept warm for 2 hours; finally, anthracite-based hard carbon sodium negative electrode material was obtained.

[0122] Among them, the difference between Comparative Example 10 and Example 1 is that the preparation method is different; in the process of preparing anthracite-based hard carbon sodium negative electrode material, Comparative Example 10 directly performs high-temperature carbonization treatment on the anthracite powder.

[0123] The anthracite-based hard carbon sodium negative electrode materials prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 10 were subjected to performance tests. Specifically, all samples were electrochemically tested using CR2032 button batteries. The mixture consists of active ingredients, SuperP, and sodium alginate, which are combined into a slurry in a ratio of 90:5:5 and coated on a copper foil. After the electrode sheet is prepared, it is vacuum dried at 80°C for 12 hours. Subsequently, the negative electrode is cut into a diameter of 12 mm. The surface density of the negative electrode is 3.6 mg / cm 2 The assembly process was carried out in a glove box filled with argon (H2O, O2 content <0.1ppm). The electrolyte was 1.0M NaPF6 EC:DMC. The electrochemical performance of the batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 10 was tested using a Shenzhen Xinwei battery tester from China for constant current discharge-charge (GCD) testing. The test was carried out at a current density of 0.02A / g, and the test results are shown in Figure 1. Figure 1 , Figure 2 As shown in Table 1. At different rates, the rate performance of the sodium ion battery prepared in Example 1 was tested, and the rate performance results are shown in Table 1. Figure 3 When the current density is 0.1A / g, the charge-discharge specific capacity and capacity retention rate of the sodium ion battery prepared in Example 1 are obtained as follows: Figure 4 shown.

[0124] Table 1:

[0125]

[0126]

[0127] It can be seen from Table 1 that the anthracite-based hard carbon sodium negative electrode materials prepared in Examples 1 to 4 of the present invention have good first charge and discharge specific capacity and first coulombic efficiency when applied to sodium ion batteries.

[0128] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0129] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0130] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing anthracite-based hard sodium carbon negative electrode material, characterized in that: The steps include: S1. Activation treatment: Activate the anthracite powder; S2. Chemical activation treatment: mixing the activated anthracite powder with an alkali solution to obtain a mixture; S3 pre-carbonization treatment: the mixture obtained in step S2 is placed under an inert gas for pre-carbonization treatment; S4. The mixture after the pre-carbonization treatment is sequentially acid-washed, then washed with water until neutral and dried; S5. High-temperature carbonization treatment: The material dried in step S4 is placed under an inert gas for high-temperature carbonization treatment to obtain an anthracite-based hard sodium carbon negative electrode material.

2. The method for preparing anthracite-based hard sodium carbon negative electrode material according to claim 1, characterized in that: The activation process is a gas activation process or a chemical solution activation process.

3. The method for preparing anthracite-based hard carbon sodium negative electrode material according to claim 2, characterized in that: The gas activation treatment comprises: placing anthracite powder under activation gas, heating it to 200-400° C. at a heating rate of 1-5° C. / min, and keeping it warm for 1-10 hours; the activation gas is one of air and ammonia.

4. The method for preparing anthracite-based hard sodium carbon negative electrode material according to claim 2, characterized in that: The chemical solution activation treatment comprises: mixing anthracite powder with an acid solution at a temperature of 60 to 80° C. for 6 to 12 hours, then washing with water until neutral and drying; the acid solution is at least one of a nitric acid solution and a phosphoric acid solution.

5. The method for preparing anthracite-based hard sodium carbon negative electrode material according to claim 1, characterized in that: The alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution; the concentration of the alkaline solution is 4 to 8 mol / L.

6. The method for preparing anthracite-based hard sodium carbon negative electrode material according to claim 1, characterized in that: The pre-carbonization treatment includes: heating to 500-900° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 1-10 hours.

7. The method for preparing anthracite-based hard sodium carbon negative electrode material according to claim 1, characterized in that: The high temperature carbonization treatment comprises: heating to 900-1500° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 1-4 hours.

8. An anthracite-based hard sodium carbon negative electrode material prepared by the method according to any one of claims 1 to 7.

9. A sodium ion battery negative electrode, characterized in that: Including the anthracite-based hard carbon sodium negative electrode material as described in claim 8.

10. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of anthracite-based hard carbon material combining pre-activation pore-forming and high-temperature carbonization

    CN112645305A

  • Soft carbon negative electrode material with disordered layer micropore structure, preparation method of soft carbon negative electrode material and sodium battery

    CN116119647A

Cited By

  • Method for preparing raw material of hard carbon negative electrode material from bituminous coal

    CN120504312A